Multicomponent reactions (MCRs): a useful access to the synthesis of benzo-fused γ-lactams - de Marigorta, Edorta Martínez; Santos, Jesús M. de Los; Ochoa de Retana, Ana M.; Vicario, Javier; Palacios, Francisco (Beilstein Journal of Organic Chemistry, 2019)
Benzo-fused γ-lactam rings such as isoindolin-2-ones and 2-oxindoles are part of the structure of many pharmaceutically active molecules. They can be often synthesized by means of multicomponent approaches and recent contributions in this field are summarized in this review. Clear advantages of these methods include the efficiency in saving raw materials and working time. However, there is still a need of new catalytic systems to allow the enantioselective preparation of these heterocycles by multicomponent reactions.
Keywords: indolin-2-ones; isoindolinones; γ-lactams; multicomponent reactions; 2-oxindoles

(untitled) - Caruano, J.; Muccioli, G. G.; Robiette, R. (Org. Biomol. Chem., 2016)

(untitled) - Speck, K.; Magauer, T. (Beilstein J. Org. Chem., 2013)

(untitled) - Sanchez, J. F.; Entwistle, R.; Corcoran, D.; Oakley, B. R.; Wang, C. C. C. (Med. Chem. Commun., 2012)

(untitled) - Yang, X.-L.; Zhang, S.; Hu, Q.-B.; Luo, D.-Q.; Zhang, Y. (J. Antibiot., 2011)

(untitled) - Moreau, A.; Couture, A.; Deniau, E.; Grandclaudon, P.; Lebrun, S. (Org. Biomol. Chem., 2005)

(untitled) - Min, J.-Y.; Kim, G. (J. Org. Chem., 2014)

(untitled) - Valencia, E.; Freyer, A. J.; Shamma, M.; Fajardo, V. (Tetrahedron Lett., 1984)

(untitled) - Li, J. C.; Li, G. P. M.; Yang, J. H.; Dai, Y.; Duan, Y. X.; Zhang, J. S. (Asian J. Chem., 2012)

(untitled) - Kamauchi, H.; Shiraishi, Y.; Kojima, A.; Kawazoe, N.; Kinoshita, K.; Koyama, K. (J. Nat. Prod., 2018)

(untitled) - Kaur, M.; Singh, M.; Chadha, N.; Silakari, O. (Eur. J. Med. Chem., 2016)

(untitled) - Zhang, H.-p.; Kamano, Y.; Ichihara, Y.; Kizu, H.; Komiyama, K.; Itokawa, H.; Pettit, G. R. (Tetrahedron, 1995)

(untitled) - De, S.; Das, M. K.; Bhunia, S.; Bisai, A. (Org. Lett., 2015)
and references cited therein.

(untitled) - Balk-Bindseil, W.; Helmke, E.; Weyland, H.; Laatsch, H. (Liebigs Ann., 1995)

(untitled) - Cui, C. B.; Kakeya, H.; Osada, H. (J. Antibiot., 1996)

(untitled) - Takahashi, I.; Kawakami, T.; Hirano, E.; Yokota, H.; Kitajima, H. (Synlett, 1996)

(untitled) - Sorbera, L. A.; Leeson, P. A.; Silvestre, J.; Castañer, J. (Drugs Future, 2001)

(untitled) - Uemura, S.; Fujita, T.; Sakaguchi, Y.; Kumamoto, E. (Biochem. Biophys. Res. Commun., 2012)
and references cited therein.

(untitled) - Badros, A. Z. (N. Engl. J. Med., 2012)

(untitled) - Shin, H.-S.; Oh, J.-A. (J. Sep. Sci., 2012)

(untitled) - Adachi, S.; Watanabe, K.; Iwata, Y.; Kameda, S.; Miyaoka, Y.; Onozuka, M.; Mitsui, R.; Saikawa, Y.; Nakata, M. (Angew. Chem., Int. Ed., 2013)
and references cited therein.

(untitled) - Riedinger, C.; Endicott, J. A.; Kemp, S. J.; Smyth, L. A.; Watson, A.; Valeur, E.; Golding, B. T.; Griffin, R. J.; Hardcastle, I. R.; Noble, M. E.; McDonnell, J. M. (J. Am. Chem. Soc., 2008)

(untitled) - Comins, D. L.; Schilling, S.; Zhang, Y. (Org. Lett., 2005)

(untitled) - Jagtap, P. G.; Southan, G. J.; Baloglu, E.; Ram, S.; Mabley, J. G.; Marton, A.; Salzman, A.; Szabó, C. (Bioorg. Med. Chem. Lett., 2004)

(untitled) - Bhardwaj, A.; Kaur, J.; Sharma, S. K.; Huang, Z.; Wuest, F.; Knaus, E. E. (Bioorg. Med. Chem. Lett., 2013)

(untitled) - Zhang, L.; Chen, X.; Liu, J.; Zhu, Q.; Leng, Y.; Luo, X.; Jiang, H.; Liu, H. (Eur. J. Med. Chem., 2012)

(untitled) - Macsari, I.; Besidski, Y.; Csjernyik, G.; Nilsson, L. I.; Sandberg, L.; Yngve, U.; Åhlin, K.; Bueters, T.; Eriksson, A. B.; Lund, P.-E.; Venyike, E.; Oerther, S.; et al. (J. Med. Chem., 2012)

(untitled) - Dobrikov, G. M.; Valcheva, V.; Stoilova-Disheva, M.; Momekov, G.; Tzvetkova, P.; Chimov, A.; Dimitrov, V. (Eur. J. Med. Chem., 2012)

(untitled) - Yoo, K.-D.; Park, E.-S.; Lim, Y.; Kang, S.-I.; Yoo, S.-H.; Won, H.-H.; Kim, Y.-H.; Yoo, I.-D.; Yoo, H.-S.; Hong, J. T.; Yun, Y.-P. (J. Pharmacol. Sci., 2012)

(untitled) - Temperini, C.; Cecchi, A.; Scozzafava, A.; Supuran, C. T. (J. Med. Chem., 2009)

(untitled) - Cai, S.-L.; Chen, Y.; Sun, W.-X.; Li, H.; Chen, Y.; Yuan, S.-S. (Bioorg. Med. Chem. Lett., 2010)

(untitled) - Cacabelos, R. (Int. J. Mol. Sci., 2017)
and references cited therein.

(untitled) - Mazzei, M. E.; Richeldi, L.; Collard, H. R. (Ther. Adv. Respir. Dis., 2015)

(untitled) - Emery, P.; Kong, S. X.; Ehrich, E. W.; Watson, D. J.; Towheed, T. E. (Clin. Ther., 2002)

(untitled) - Kauffman, R. F.; Robertson, D. W.; Franklin, R. B.; Sandusky, G. E., Jr; Dies, F.; McNay, J. L.; Hayes, J. S. (Cardiovasc. Drug Rev., 1990)

(untitled) - Bethke, T.; Brunkhorst, D.; von der Leyen, H.; Meyer, W.; Nigbur, R.; Scholz, H. (Naunyn-Schmiedeberg's Arch. Pharmacol., 1988)

(untitled) - Nagamine, J.; Nagata, R.; Seki, H.; Nomura-Akimaru, N.; Ueki, Y.; Kumagai, K.; Taiji, M.; Noguchi, H. (J. Endocrinol., 2001)

(untitled) - Faivre, S.; Demetri, G.; Sargent, W.; Raymond, E. (Nat. Rev. Drug Discovery, 2007)

(untitled) - London, C. A.; Malpas, P. B.; Wood-Follis, S. L.; Boucher, J. F.; Rusk, A. W.; Rosenberg, M. P.; Henry, C. J.; Mitchener, K. L.; Klein, M. K.; Hintermeister, J. G.; Bergman, P. J.; Couto, G. C.; et al. (Clin. Cancer Res., 2009)

(untitled) - Prakash, C. R.; Theivendren, P.; Raja, S. (Pharmacol. Pharm., 2012)

(untitled) - Rottmann, M.; McNamara, C.; Yeung, B. K. S.; Lee, M. C. S.; Zou, B.; Russell, B.; Seitz, P.; Plouffe, D. M.; Dharia, N. V.; Tan, J.; Cohen, S. B.; Spencer, K. R.; et al. (Science, 2010)

(untitled) - Yan, L.; Xie, F.; Lu, J.; Ni, Q.; Shi, C.; Tang, C.; Yang, J. (BMC Gastroenterol., 2015)

(untitled) - Izumi, Y.; Miura, K.; Iwao, H. (J. Pharmacol. Sci., 2014)

(untitled) - Augusto Ribeiro Do Valle, L.; Raposo De Melo, P.; Florêncio De Salles Gomes, L.; Morato Proença, L. (Lancet, 1965)

(untitled) - Mugishima, T.; Tsuda, M.; Kasai, Y.; Ishiyama, H.; Fukushi, E.; Kawabata, J.; Watanabe, M.; Akao, K.; Kobayashi, J. (J. Org. Chem., 2005)
and references cited therein.

(untitled) - Kushida, N.; Watanabe, N.; Okuda, T.; Yokoyama, F.; Gyobu, Y.; Yaguchi, T. (J. Antibiot., 2007)

(untitled) - Kaur, M.; Singh, P. (Bioorg. Med. Chem. Lett., 2019)

(untitled) - Tokala, R.; Thatikonda, S.; Vanteddu, U. S.; Sana, S.; Godugu, C.; Shankaraiah, N. (ChemMedChem, 2018)

(untitled) - Zhou, Y.; Ju, Y.; Yang, Y.; Sang, Z.; Wang, Z.; He, G.; Yang, T.; Luo, Y. (J. Antibiot., 2018)

(untitled) - Zhang, J.; Yu, P.; Li, S.-Y.; Sun, H.; Xiang, S.-H.; Wang, J.; Houk, K. N.; Tan, B. (Science, 2018)

(untitled) - Wang, Q.; Wang, D.-X.; Wang, M.-X.; Zhu, J. (Acc. Chem. Res., 2018)

(untitled) - Ibarra, I. A.; Islas-Jácome, A.; González-Zamora, E. (Org. Biomol. Chem., 2018)

(untitled) - Kazemizadeh, A. R.; Ramazani, A. (Curr. Org. Chem., 2012)

(untitled) - van Berkel, S. S.; Bögels, B. G. M.; Wijdeven, M. A.; Westermann, B.; Rutjes, F. P. J. T. (Eur. J. Org. Chem., 2012)

(untitled) - Hall, D. G.; Rybak, T.; Verdelet, T. (Acc. Chem. Res., 2016)

(untitled) - Sadjadi, S.; Heravi, M. M.; Nazari, N. (RSC Adv., 2016)

(untitled) - Rotstein, B. H.; Zaretsky, S.; Rai, V.; Yudin, A. K. (Chem. Rev., 2014)

(untitled) - Alonso, C.; Fuertes, M.; Martín-Encinas, E.; Selas, A.; Rubiales, G.; Tesauro, C.; Knudssen, B. K.; Palacios, F. (Eur. J. Med. Chem., 2018)

(untitled) - Alonso, C.; Martín-Encinas, E.; Rubiales, G.; Palacios, F. (Eur. J. Org. Chem., 2017)

(untitled) - Ghashghaei, O.; Masdeu, C.; Alonso, C.; Palacios, F.; Lavilla, R. (Drug Discovery Today: Technol., 2018)

(untitled) - del Corte, X.; Maestro, A.; Vicario, J.; Martinez de Marigorta, E.; Palacios, F. (Org. Lett., 2018)

Multicomponent Reactions in Organic Synthesis - Zhu, J.; Wang, Q.; Wang, M.-X. (Wiley-VCH, 2015)

(untitled) - Marson, C. M. (Chem. Soc. Rev., 2012)

(untitled) - Dömling, A.; Wang, W.; Wang, K. (Chem. Rev., 2012)

(untitled) - de Graaff, C.; Ruijter, E.; Orru, R. V. A. (Chem. Soc. Rev., 2012)

High-Throughput Lead Optimization in Drug Discovery in Critical Reviews in Combinatorial Chemistry - Kshirsagar, T. (CRC Press, 2008)

(untitled) - Burke, M. D.; Schreiber, S. L. (Angew. Chem., Int. Ed., 2004)

(untitled) - Bisai, V.; Unhale, R. A.; Suneja, A.; Dhanasekaran, S.; Singh, V. K. (Org. Lett., 2015)

(untitled) - Karmakar, R.; Suneja, A.; Bisai, V.; Singh, V. K. (Org. Lett., 2015)

(untitled) - Bisai, V.; Suneja, A.; Singh, V. K. (Angew. Chem., Int. Ed., 2014)

(untitled) - Zeng, X.; Ni, Q.; Raabe, G.; Enders, D. (Angew. Chem., Int. Ed., 2013)

(untitled) - Zeng, X. (Chem. Rev., 2013)

(untitled) - Alonso, C.; González, M.; Palacios, F.; Rubiales, G. (J. Org. Chem., 2017)

(untitled) - Liu, L.; Qiang, J.; Bai, S.-H.; Sung, H.-L.; Miao, C.-B.; Li, J. (Adv. Synth. Catal., 2017)

(untitled) - Nozawa-Kumada, K.; Kadokawa, J.; Kameyama, T.; Kondo, Y. (Org. Lett., 2015)

(untitled) - Verma, A.; Patel, S.; Meenakshi, M.; Kumar, A.; Yadav, A.; Kumar, S.; Jana, S.; Sharma, S.; Prasad, C. D.; Kumar, S. (Chem. Commun., 2015)
and references cited therein.

(untitled) - Wang, P.-M.; Pu, F.; Liu, K.-Y.; Li, C.-J.; Liu, Z.-W.; Shi, X.-Y.; Fan, J.; Yang, M.-Y.; Wei, J.-F. (Chem. – Eur. J., 2016)

(untitled) - Irudayanathan, F. M.; Noh, J.; Choi, J.; Lee, S. (Adv. Synth. Catal., 2014)

(untitled) - Park, K.; Palani, T.; Pyo, A.; Lee, S. (Tetrahedron Lett., 2012)

(untitled) - Sarkar, S.; Chatterjee, N.; Roy, M.; Pal, R.; Sarkar, S.; Sen, A. K. (RSC Adv., 2014)

(untitled) - Mancuso, R.; Ziccarelli, I.; Armentano, D.; Marino, N.; Giofrè, S. V.; Gabriele, B. (J. Org. Chem., 2014)

(untitled) - Sun, L. X.; Zeng, T.; Jiang, D.; Dai, L.-Y.; Li, C.-J. (Can. J. Chem., 2012)

(untitled) - Zhang, H.; Leng, Y.; Liu, W.; Duan, W. (Synth. Commun., 2012)

(untitled) - Sashidhara, K. V.; Singh, L. R.; Palnati, G. R.; Avula, S. R.; Kant, R. (Synlett, 2016)

(untitled) - Han, F.-Z.; Su, B.-B.; Jia, L.-N.; Wang, P.-W.; Hu, X.-P. (Adv. Synth. Catal., 2017)

(untitled) - Dhanasekaran, S.; Kayet, A.; Suneja, A.; Bisai, V.; Singh, V. K. (Org. Lett., 2015)

(untitled) - Chen, T.; Cai, C. (New J. Chem., 2017)

(untitled) - Ley, S. V.; Taylor, S. J. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Zhang, J.; Jacobson, A.; Rusche, J. R.; Herlihy, W. (J. Org. Chem., 1999)

(untitled) - Shaabani, A.; Hajishaabanha, F.; Mahyari, M.; Mofakham, H.; Ng, S. W. (Tetrahedron, 2011)

(untitled) - Esmaeili-Marandi, F.; Yavari, I.; Saeedi, M.; Mahdavi, M.; Shafiee, A. (Helv. Chim. Acta, 2016)

(untitled) - Kajanus, J.; Jacobson, I.; Åstrand, A.; Olsson, R. I.; Gran, U.; Björe, A.; Fjellström, O.; Davidsson, Ö.; Emtenäs, H.; Dahlén, A.; Löfberg, B.; Yuan, Z.-Q.; et al. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Zhang, Y.; Ao, Y.-F.; Huang, Z.-T.; Wang, D.-X.; Wang, M.-X.; Zhu, J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Nammalwar, B.; Muddala, N. P.; Murie, M.; Bunce, R. A. (Green Chem., 2015)

(untitled) - Chen, T.; Cai, C. (Catal. Commun., 2016)

(untitled) - Dabral, S.; Turberg, M.; Wanninger, A.; Bolm, C.; Hernández, J. G. (Molecules, 2017)

(untitled) - Kumar, K. S.; Kumar, P. M.; Kumar, K. A.; Sreenivasulu, M.; Jafar, A. A.; Rambabu, D.; Krishna, G. R.; Reddy, C. M.; Kapavarapu, R.; Shivakumar, K.; Priya, K. K.; Parsa, K. V. L.; et al. (Chem. Commun., 2011)

(untitled) - Sashidhara, K. V.; Palnati, G. R.; Dodda, R. P.; Avula, S. R.; Swami, P. (Synlett, 2013)

(untitled) - Reddy, G. R.; Reddy, T. R.; Chary, R. G.; Joseph, S. C.; Mukherjee, S.; Pal, M. (Tetrahedron Lett., 2013)

(untitled) - Madhubabu, M. V.; Shankar, R.; Reddy, G. R.; Rao, T. S.; Rao, M. V. B.; Akula, R. (Tetrahedron Lett., 2016)

(untitled) - Guo, S.; Zhai, J.; Wang, F.; Fan, X. (Org. Biomol. Chem., 2017)

(untitled) - Zhang, J.; Zhang, F.; Lai, L.; Cheng, J.; Sun, J.; Wu, J. (Chem. Commun., 2018)

(untitled) - Kaicharla, T.; Thangaraj, M.; Biju, A. T. (Org. Lett., 2014)

(untitled) - Liu, L.; Bai, S.-H.; Li, Y.; Wang, L.-X.; Hu, Y.; Sung, H.-L.; Li, J. (J. Org. Chem., 2017)

(untitled) - Liu, L.; Bai, S.-H.; Li, Y.; Ding, X.-D.; Liu, Q.; Li, J. (Adv. Synth. Catal., 2018)

(untitled) - Li, J.; Bai, S.; Li, Y.; Wang, Z.; Huo, X.; Liu, L. (J. Org. Chem., 2018)

(untitled) - Shiri, M.; Ranjbar, M.; Yasaei, Z.; Zamanian, F.; Notash, B. (Org. Biomol. Chem., 2017)

(untitled) - Torres, G. M.; De La Higuera Macias, M.; Quesnel, J. S.; Williams, O. P.; Yempally, V.; Bengali, A. A.; Arndtsen, B. A. (J. Org. Chem., 2016)

(untitled) - Grigg, R.; Gai, X.; Khamnaen, T.; Rajviroongit, S.; Sridharan, V.; Zhang, L.; Collard, S.; Keep, A. (Can. J. Chem., 2005)

(untitled) - Yin, H.; Skrydstrup, T. (J. Org. Chem., 2017)

(untitled) - Zhou, K.; Xia, H.; Wu, J. (Org. Chem. Front., 2016)

(untitled) - Dondas, H. A.; Belveren, S.; Poyraz, S.; Grigg, R.; Kilner, C.; Ferrándiz-Saperas, M.; Selva, E.; Sansano, J. M. (Tetrahedron, 2018)

(untitled) - Wang, H.; Sun, S.; Cheng, J. (Org. Lett., 2017)

(untitled) - Yu, Y.; Shin, K. J.; Seo, J. H. (J. Org. Chem., 2017)

(untitled) - Park, S.; Lee, J.; Shin, K. J.; Oh, E.; Seo, J. H. (Molecules, 2017)

(untitled) - Park, S.; Shin, K. J.; Seo, J. H. (Synlett, 2015)

(untitled) - Boominathan, M.; Nagaraj, M.; Muthusubramanian, S.; Bhuvanesh, N. (RSC Adv., 2014)